Film noir portraits - Nourmand, Tony 1965- (Reel Art Press, 2022)
With its singular focus on the very best portrait photography of the 1940s and 1950s Hollywood film noir era, every page of this coffee-table volume is rich in brooding atmosphere. The portraits gathered here, of actors such as Rita Hayworth, Orson Welles, Humphrey Bogart, Lauren Bacall, Barbara Stanwyck, Robert Mitchum, Jane Greer, Gene Tierney, Burt Lancaster, Ava Gardner, Jack Palance, Joan Crawford and Richard Widmark, were taken by premier studio photographers such as Robert Coburn, Ernest Bachrach and A.L. "Whitey" Schafer. Their remarkable ability to exaggerate the play of shadow and light to dramatic effect is the reason that their work still has the same ability to arrest the viewer as it did in the 1940s. The photographs remain some of the most innovative and striking portraits in the history of cinema. Carefully curated, the photographs are taken from the collection of MPTV, one of the world's most exclusive archives of entertainment photography. The book includes many previously unseen images, including hitherto unpublished outtakes from The Night of the Hunter (1955) and Sweet Smell of Success (1957); and classic moments from films such as Gilda (1946), Double Indemnity (1944), The Lady from Shanghai (1947) and celebrated B-noirs such as Gun Crazy (1950) and The Hitch-Hiker (1953). Reel Art Press' exquisite print quality serves to emphasize the timeless power of the black-and-white studio portraiture
Keywords: Geschichte 1940-1960; Porträtfotografie; Schwarzweißfotografie; Schauspieler -- Motiv; Portrait photography; Black-and-white photography; Film noir; Motion picture actors and actresses / Portraits; Portraits (Photographie); Photographie en noir et blanc; Films noirs; black-and-white photography; Motion picture actors and actresses; Portraits; Bildband